PENDIDIKAN ILMU PENGETAHUAN SOSIAL BERBASIS C3 (COLLEGE, CARRIER, CIVIC LIFE) DAN LIFE SKILL UNTUK MEMBENTUK KARAKTER SISWA SEKOLAH MENENGAH PERTAMA - Anita Rinawati; Ary Purwantiningsih (Universitas Muria Kudus, 2021)
The purpose of this study is to analyze the application of C3-based Social Studies Education (College, Carrier, Civic Life) and Life Skills to form character in junior high school students during the pandemic. The research method used is qualitative. The research subjects were students and social studies teachers of SMP Negeri 1 in Purworejo Regency. Data collection techniques used were observation and online interviews to prevent transmission. Data collection was carried out in December 2020. Test the validity of the data using the triangulation technique. In the data analysis technique used data analysis includes 1) data reduction; 2) Data Presentation; and 3) Drawing conclusions. The results of the social studies education model by referring to the C3 framework and incorporating elements of Life Skills are very useful for the lives of students, including 1) Students will have a broad meaning of life skills, 2) Students are able to deal proactively and reactively in order to find solutions to problems, 3) The C3 Social Studies framework can be a guide for students' readiness to enter higher education, career preparation and community life as well as critical thinking skills, problem solving abilities, and collaborative skills needed during the current pandemic.